External Debt and Economic Reform : Does a Pain Reliever Delay the Necessary Treatment? - Vamvakidis, Athanasios (Washington, D.C. : International Monetary Fund, 2007)
Recent literature argues that conflict in shifting adjustment costs between different socioeconomic groups delays necessary reforms and finds that such reforms often follow economic crises. This paper expands these models by including external borrowing by the private sector and shows that this may lead to a further delay in economic reform. Empirical evidence based on a large panel of developing and emerging economies supports this argument and shows that the result is slower economic growth. External financing sometimes acts like a "pain reliever," postponing the much needed "treatment" of a "sick" economy by reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet